Penguatan Regulasi Uji Kelayakan dan Kepatutan dalam Pengangkatan Komisaris BUMN - Ayu Kholifah; Fatihani Baso (Fakultas Hukum Universitas Jambi, 2022)
The fit and proper test (FPT) in filling the position of the board of commissioners at State-Owned Enterprises (SOEs) currently only applies to the financial service institution (LJK) cluster, and not to other clusters. Whereas, FPT aims to identify the suitability and properness of candidates, and avoids the impression of candidates filling in on the basis of political closeness to the authorities. This article urges that FPT be applied in filling the positions of the board of commissioners of all SOEs, not limited to the LJK cluster. First, due to the lack of LJK clusters, which are only 19.6 percent of the total 98 SOEs in early 2021. Second, FPT is an important instrument in supporting the application of GCG principles to SOEs, considering the inherent GCG principles on boards must be applied starting from the selection process. Third, FPT is expected to attract professional commissioners. This article encourages the strengthening of FPT regulations for all prospective BUMN commissioners carried out by independent institutions that professionally assess and measure the competence and integrity of candidates, then the FPT guidelines must be stated in a Government Regulation as stipulated in Article 16 paragraph (4) PP No. 45 Year 2005. Abstrak Uji kelayakan dan kepatutan, atau lebih dikenal fit and proper test (FPT), dalam pengisian jabatan dewan komisaris pada Badan Usaha Milik Negara (BUMN) saat ini hanya berlaku pada klaster lembaga jasa keuangan (LJK), dan tidak pada klaster lainnya. Padahal FPT bertujuan untuk mengidentifikasi kelayakan dan kepatutan para calon, dan menghindari kesan calon yang mengisi atas dasar kedekatan politik dengan penguasa. Artikel ini mendorong agar FPT diberlakukan dalam pengisian jabatan dewan komisaris seluruh BUMN, tidak terbatas pada klaster LJK. Pertama, hal ini disebabkan karena minimnya klaster LJK yang hanya 19,6 persen dari keseluruhan 98 jumlah BUMN pada awal 2021. Kedua, FPT merupakan instrumen penting dalam mendukung penerapan prinsip GCG pada BUMN, mengingat prinsip GCG yang melekat pada boards sudah harus diterapkan mulai dari proses pemilihan. Ketiga, FPT diharapkan dapat menjaring calon komisaris yang profesional. Artikel ini mendorong penguatan regulasi FPT bagi seluruh calon komsiaris BUMN yang dilakukan oleh lembaga independen yang secara profesional menilai dan mengukur kompetensi dan integritas para calon, kemudian pedoman FPT harus dituangkan dalam Peraturan Menteri sebagaimana diatur dalam Pasal 16 ayat (4) Peraturan Pemerintah No. 45 Tahun 2005.